An approach based on risk to dimensioning virtual organizations. Issue 1 (16th August 2017) - Ferreira, Jonathan Emannoel; Fiorese, Adriano
Abstract: In an increasingly competitive market, small and medium enterprises have the temporarily option to divide their core competencies in sub‐competences. In fact, this is the purpose of so‐called virtual organizations (VOs), which aim to attend a particular goal joining partner forces. However, when these VOs are created, it is necessary to deal with the maximum number of participants involved in the process and the risk involved in these relationships, which should be measured through a well‐defined process. This paper aims to present an approach to dimensioning the maximum number of participants involved in the formation of a VO composed of several service providers. This approach is based on the overall risk level of the participants and uses different risk analysis methods to assess the suitable number of participants to be part of a VO.